Hermits and recluses in English society, 950 - 1200 - Licence, Tom (Oxford University Press, 2011)
The Anglo-Saxon and European background. The Anglo-Saxon inheritance, 650-950 ; The wider European context, 950-1100 -- The rise of the hermit in England. The eremitic ideal, c.950-c.1050 ; Ascetics and hermits, c.1050-c.1080 ; Hermits and their admirers, c.1080-c.1120 -- The rise of the recluse. Recluses in the German Empire ; The rise of the recluse in England -- How anchorites made a living. Anchorites and their patrons ; Pioneers in the wilderness ; Living in a cell -- Eradicating sin, in theory. Model 1 : exile as a satisfactory penance ; Model 2 : exile as the preliminary phase of purgation ; Model 3 : anachoresis as the imitatio Christi ; Modelling reclusion ; Models outside the monasteries -- Eradicating sin, in practice. Escaping the world ; Purifying the mind and overcoming the flesh ; Warning with demons ; Forbearance in the vocation -- How anchorites helped others. Inspiring repentance ; Intercession ; Clients and confraternities ; Mediating God's power -- How anchorites became saints